DEVELOPMENT OF THE LATEST CURRICULUM-BASED LEARNING MODEL TO IMPROVE STUDENTS' DIGITAL LITERACY AND CRITICAL THINKING SKILLS IN THE INFORMATION TECHNOLOGY ERA - Shidqiyah; Bahrun Thalib; Rivaldi Wiratama; Sitti Nur Alam; Riyanto (International Journal of Teaching and Learning, 2023)
In the rapidly evolving Information Technology era, students' demand for digital literacy and critical thinking skills has never been more pressing. This abstract presents an overview of the development of the latest curriculum-based learning model designed to enhance students' digital literacy and critical thinking abilities. Our model, tailored for the modern educational landscape, strongly emphasizes integrating technology into the learning process. It leverages a combination of innovative pedagogical approaches, updated content, and interactive tools to engage students in the digital world. By focusing on digital literacy, students are equipped with the skills to navigate, evaluate, and create digital content effectively while fostering an understanding of online safety and ethical behavior. Furthermore, the model fosters critical thinking through project-based learning, problem-solving activities, and collaborative assignments. It encourages students to analyze information critically, synthesize ideas, and make informed decisions. Integrating real-world case studies and hands-on experiences ensures that students can apply their knowledge in practical situations.